Meningkatkan Kemampuan Konsentrasi Anak Melalui Media Puzzle pada Anak Kelompok B di RA Umdi Al-Ihsan Parepare - Palintan, Tien Asmara; Nurul Asqia; Hariska (Program Studi Pendidikan Islam Anak Usia Dini, 2022)
The purpose of this research is to improve children's concentration ability by using puzzle media. This research method is a qualitative research method using a case study approach in data collection. The methods of collecting and managing data are using observation, documentation and interview methods. The results of the study are by using puzzle media the ability to concentrate on children increases, where an educator uses the method of playing while learning so that children can concentrate and can train children's patience in compiling puzzle media.